Karyological studies of 10 Cirsium sect. Epitrachys (Asteraceae) species from Turkey - Yuksel, Eda; Kiran, Yasar; Sahin, Ahmet; Yildiz, Bayram; Arabaci, Turan (Tubitak Scientific & Technological Research Council Turkey, 2013)
Detailed karyotype properties were established for 10 Cirsium Mill. sect. Epitrachys DC. species distributed in Turkey. The species Cirsium ligulare Boiss., C. sintenisii Freyn, C. boluense P. H. Davis & Parris, C. eriophorum (L.) Scop., C. steirolepis Petr., C. baytopae P. H. Davis & Parris, C. poluninii P. H. Davis & Parris, C. ciliatum (Murray) Moench subsp. szovitsii (K. Koch) Petr., C. ellenbergii Bornm., and C. vulgare (Savi) Ten. have the somatic chromosome number 2n = 2x = 34, whereas C. sintenisii and C. vulgare showed 2n = 4x = 68. The chromosome numbers of C. sintenisii, C. boluense, C. baytopae, C. poluninii, and C. ellenbergii are newly reported here. Karyotype analysis indicated that chromosomes of Cirsium taxa generally have median region (m) and rarely median point (M) and submedian region (sm) karyotypes. The findings for each of the analyzed taxa are compared with the results of previous studies.
Keywords: Chromosome number; Cirsium; karyotypes; new count; Turkey